Living Through History: The Abolition of the Slave Trade - Leas, Allan (B. T Batsford Ltd, 1989)
The slave trade between Europe, West Africa, and the Carribean was of great economic importance to eighteenth century Britain, but was abolished in the nineteenth century.
Keywords: Juvenile literature-Anti slavery movements-Slave trade-History-Slavery-Great Britain-Non fiction